Depression in Physicians: An Overlooked Issue in Mental Health (Journal of Enam Medical College, 2020)
Depression is a common mental disorder that presents with depressed mood, loss of interest, feelings of guilt or low self-esteem. It affects an estimated one in 15 adults (6.7%) in any given year. One in six people (16.6%) will experience depression at some point in their lifetime. It can strike at any time; but usually it first appears during the late teens to mid-20s. Women usually experience depression more than men. Depression is one of the most common mental health issues among physicians worldwide due to high-intensity training and work overload. Recent systematic reviews and meta-analysis indicated that the prevalence of depression among physicians worldwide was around 28.8% which is quite higher than in the rest of the general population. Depressed physician makes more medical error than others. The burden of depression could lead to a low quality of life, ultimately suicidal attempts. So identifying risk factors for depression must be addressed and solved properly with utmost priority. This article reviews the prevalence of depression in physicians based on recently published literature related to this arena.J Enam Med Col 2020; 10(1): 39-42